Clinical and Histopathological Findings of Six Cases of Extrapulmonary Tuberculosis - Widya Rukmi, Kartika; Sasongko, Aries; Dwinanda Suyuthie, Heldrian; Untari Dewi, Trisni; Kiasati Chandra Syahbunan, Khansa; Desdiani, Desdiani (GALENICAL : Jurnal Kedokteran dan Kesehatan Mahasiswa Malikussaleh, 2025)
Extrapulmonary Tuberculosis (EPTB), caused by Mycobacterium tuberculosis, affects organs other than the lungs, most commonly the lymph nodes and pleura. Although pulmonary tuberculosis (TB) is more prevalent in Indonesia, EPTB remains a significant yet often underreported condition. Its diagnosis depends on histological, microbiological, and clinical evidence, with treatment typically initiated based on a physician's judgment. The diverse symptoms of EPTB, depending on the affected organs, contribute to its frequent underdiagnosis. Histopathological examination is the gold standard for EPTB diagnosis, particularly valuable when microbiological tests yield inconclusive results, and is characterized by well- and poorly-organized granulomas. Methods this study reviewed six cases of EPTB, focusing on clinical presentations, radiological findings, and histopathological results. The patients presented with lumps in various locations, including the wrist, spine, neck, abdomen, thigh/groin, and scrotum. Ultrasound and CT scan were employed to assess organ involvement, and tissue biopsies were analyzed histopathologically. The cases exhibited diverse symptoms and clinical findings. Blood tests and chest radiographs were normal in all patients. Imaging studies revealed nonspecific hypoechoic patterns, omental thickening, and prominent mesenteric lymph nodes in some cases. Histopathological analysis consistently identified granulomas in all biopsy samples. Some specimens showed extensive caseous necrosis with Langhans giant cells, while others exhibited fibrotic tissue with well-formed granulomas and minimal caseous necrosis. Conclusion diagnosing EPTB remains challenging due to its paucibacillary nature and the limitations of current diagnostic tools. Histopathological and microbiological evaluations of biopsy specimens are essential to improving diagnostic accuracy and reducing the morbidity and mortality associated with EPTB.